2023
DOI: 10.1021/acsnano.3c01068
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Au25 Clusters with Single-Crystal Structure for Mitochondria-Targeting Radioimmunotherapy

Abstract: Atomically precise gold clusters play an important role in the development of high-Z-element-based radiosensitizers, due to their intriguing structural diversity and advantages in correlating structures and properties. However, the synthesis of gold clusters with both water-solubility and single-crystal structure remains a challenge. In this study, atomically precise Au25(S-TPP)18 clusters (TPP-SNa = sodium 3-(triphenylphosphonio)­propane-1-thiolate bromide) showing both mitochondria-targeting ability and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The use of Pt nanoassemble-enriched MOFs for the treatment of breast cancer was reported by Zhang et al, heterojunction structured Wo2.9-WSe2-PEG nanoparticles for radiotherapy/PTT/immune checkpoint blockade immunotherapy was demonstrated by Dong et al, a nutritional immunotherapy nanosystem, and Arg-doped PCN-224 composed of Zr and TCPP followed by gelatin coating was designed by Zhang et al for RDT and nitric oxide production stimulators. Hua et al demonstrated Au 25 clusters with a mitochondria-targeting moiety, 3-(triphenylphosphonio)­propane-1-thiolate bromide) or TPP, for radioimmunotherapy . Considering that the effects of radiotherapy-induced ICD are not sufficient for the eradication of distant tumors, the antiprogrammed death ligand 1 encapsulated MnO 2 with surface HA modification as a checkpoint inhibitor delivery platform combined with radiation was designed to overcome this limitation …”
Section: Stimuli-responsive Polymeric Nanomedicine For Cancer Immunot...mentioning
confidence: 99%
“…The use of Pt nanoassemble-enriched MOFs for the treatment of breast cancer was reported by Zhang et al, heterojunction structured Wo2.9-WSe2-PEG nanoparticles for radiotherapy/PTT/immune checkpoint blockade immunotherapy was demonstrated by Dong et al, a nutritional immunotherapy nanosystem, and Arg-doped PCN-224 composed of Zr and TCPP followed by gelatin coating was designed by Zhang et al for RDT and nitric oxide production stimulators. Hua et al demonstrated Au 25 clusters with a mitochondria-targeting moiety, 3-(triphenylphosphonio)­propane-1-thiolate bromide) or TPP, for radioimmunotherapy . Considering that the effects of radiotherapy-induced ICD are not sufficient for the eradication of distant tumors, the antiprogrammed death ligand 1 encapsulated MnO 2 with surface HA modification as a checkpoint inhibitor delivery platform combined with radiation was designed to overcome this limitation …”
Section: Stimuli-responsive Polymeric Nanomedicine For Cancer Immunot...mentioning
confidence: 99%
“…Metal nanoclusters have attracted wide attention because of their atom-precise structures and quantum size effects, which provide an ideal platform for investigating the connection between simple metal complexes and bulk metal nanoparticles. 1–16 In addition, their potential applications in optics, 17–20 catalysis, 21–25 and biomedicine 26–28 encourage us to synthesize novel structured nanoclusters to exploit versatile properties. Among these, nanoclusters with valence electron structures similar to atomic electron structures are considered “superatomic nanoclusters”.…”
Section: Introductionmentioning
confidence: 99%
“…Hua et al reported cationic water-soluble Au 25 clusters for mitochondria-targeting radioimmunotherapy. 20 The introduction of cationic units in ligands enabled the Au 25 (S-TPP) 18 clusters to have gratifying ability to target mitochondria, which significantly enhanced their tumor killing efficacy at low doses of X-ray compared with Au 25 (SG) 18 .…”
Section: Introductionmentioning
confidence: 99%